Nurturing potential: the positive effects of hydroponic farming on people with disabilities (PWD) - Saarani, Puteri Sidrotul Nabihah; Abdul Tharim, Asniza Hamimi; Che Ahmad, Asmalia; Abdul Rahman, Norhafizah; Mohamed Saraf, Mohamad Haizam; Jaffar, Noraidawati; Mohd Noor, Siti Nur Aishah; Mohamed Yusof, Nur Fatiha; Jaafar, Adnin Syaza; Saharuddin, Shafikah; Abdullah @ Dolah, Noor Anisah; Ramly, Mohd Khairul Amri (Universiti Teknologi MARA, Kedah, 2024)
Hydroponic farming has emerged as a modern alternative to traditional agriculture, offering numerous benefits such as space savings, water conservation, and the ability to grow crops in urban settings. For persons with disabilities (PWD), hydroponics provides a more accessible and inclusive farming method by eliminating many of the physical barriers associated with traditional farming. This study examines the positive effects of hydroponic farming on PWD, focusing on emotional well-being, skill development, and community engagement. The main issue addressed is the need for inclusive farming techniques that accommodate the physical limitations of PWD while promoting their well-being and empowerment. The objective of the study is to explore how activity-based hydroponic programs can enhance the lives of PWD by providing practical skills, emotional support, and social integration. A mixed-method approach was employed, including hands-on training sessions where PWD trainees taught community members the steps of hydroponic farming, followed by interviews with participants and stakeholders to assess the program's effectiveness. Analysis of the data revealed that hydroponic farming activities significantly boosted the emotional well-being of PWD by fostering positive emotions and reducing stress. The program also enhanced essential skills such as communication, basic calculations, and knowledge transfer, which contributed to the trainees' confidence and independence. Furthermore, community engagement through the program helped reduce social isolation and promoted inclusion. The study concludes by proposing future research on incorporating gamification-based activities to further enhance engagement and learning outcomes in hydroponic programs for PWD.